Uji Antidiabetik Ekstrak Buah Pare (Momordica charantia L.) terhadap Penurunan Kadar Glukosa Darah pada Mencit yang Diinduksi Streptozotocin - Parawansah Parawansah; Nuralifah Nuralifah; Andi Noor Kholidha (MEDULA JURNAL ILMIAH FAKULLTAS KEDOKTERAN UNIVERSITAS HALU OLEO, 2017)
ABSTRACT Diabetes mellitus is a chronic disease in which the patient has excess glucose levels in the blood. Pare (Momordica charantia L.) is one of the plants that have efficacy in treating various diseases one of them is antidiabetes. Activity of active substances from the pare may play a role in lowering blood sugar levels. This research is done to know the effect of increasing concentration of pare extract to decrease blood glucose level in mice induced by streptozotocin.This study was experimental laboratory, the study was done by measured  the initial blood sugar level in mice, sugar content after induction of steptozotosin, and after administration of 100 mg / kgBW extract test, 250 mg / kgBW and 400 mg / kgBW with observation time for 7 days , as well as gave metformin suspension as a positive control.The results showed that the optimum value of antidiabetic activity of ethanol extract of pare fruit at a concentration of 400 mg / kgBW and had an average decrease of 122 mg / dl.Keywords: Antidiabetes, Momordica charantia L., Streptozotocin